2010
DOI: 10.1117/12.842449
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic cages of GaN nanoclusters doped with Gd and Nd

Abstract: We report results of ab initio calculations on (GaN) n nanoclusters with n = 12, 16, 22, and 24 using generalized gradient approximation (GGA) for the exchange-correlation energy. We find cage structures of GaN clusters to be lower in energy as compared to bulk fragments which have been fully optimized. Selected cages have been doped with Gd and Nd atoms by substituting Gd and Nd on Ga sites, respectively. The atomic structures of such doped nanoclusters have been optimized using spin-polarized GGA and by incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…We performed calculations for one and two Eu atoms doped in (GaN) n nanoparticles and also for Eu atoms co-doped with a Si atom in (GaN) n nanoparticles (n ¼ 12, 13, and 32). The optimized structures for the case of two Eu doping show a small decrease in the binding energy compared with one Eu doping as it was also found 34 for Gd and Nd doping in small GaN nanoparticles. Therefore, it is expected that clustering of Eu atoms may not occur in nanoparticles, though the doping may not be limited to one Eu ion per nanocrystal.…”
Section: Methods Of Calculationssupporting
confidence: 67%
“…We performed calculations for one and two Eu atoms doped in (GaN) n nanoparticles and also for Eu atoms co-doped with a Si atom in (GaN) n nanoparticles (n ¼ 12, 13, and 32). The optimized structures for the case of two Eu doping show a small decrease in the binding energy compared with one Eu doping as it was also found 34 for Gd and Nd doping in small GaN nanoparticles. Therefore, it is expected that clustering of Eu atoms may not occur in nanoparticles, though the doping may not be limited to one Eu ion per nanocrystal.…”
Section: Methods Of Calculationssupporting
confidence: 67%
“…reported nonmagnetic RE element Sc‐doped AlN nanomaterials showing RT‐FM behavior and proposed that the formation energy of cation vacancy can be reduced by doping nonmagnetic elements leading to ferromagnetism in semiconductors. Very recently, ab initio calculations on magnetic properties of Nd‐doped GaN nanoclusters revealed that the coupling between the RE atoms is found to be FM with the total magnetic moment of 3 μB per Nd atom . Also, magnetic properties of Gd‐doped GaN nanopowders have been found to exhibit Curie–Weiss behavior of magnetic susceptibility .…”
Section: Resultsmentioning
confidence: 99%